2001
DOI: 10.1002/pola.10072
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the structural parameters of a series of fluoromonoacrylates on the surface properties of cured films

Abstract: A series of fluorinated acrylates [F(CF 2 ) q O(CH 2 ) p OOCOCHACH 2 , where q ϭ 8 and p ϭ 2 Ϭ 11) were synthesized and used as comonomers in the photopolymerization of acrylic systems. These fluoroacrylates were synthesized in a three-step procedure through the radical addition of perfluoroalkyliodides to an unsaturated alcohol followed by their acrylation. The mixtures, containing up to 0.8% (w/w) of the comonomers, produced transparent films after UV curing; they showed changes in the surface properties as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 19 publications
4
44
0
1
Order By: Relevance
“…[1][2][3][4][5] In recent years, a lot of investigations have been conducted on the fluorine-containing acrylate latex due to their special surface property, good adhesion to matrices, and environmental friendly properties. [6][7][8][9][10] Although there are obvious advantages and benefits in generating fluorine-containing polymers via emulsion polymerization, their incorporation into colloidal particles is difficult to handle. The primary reason is the immiscibility between hydrophobic C-F entities and the continuous aqueous phase resulting from large surface tension differences.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] In recent years, a lot of investigations have been conducted on the fluorine-containing acrylate latex due to their special surface property, good adhesion to matrices, and environmental friendly properties. [6][7][8][9][10] Although there are obvious advantages and benefits in generating fluorine-containing polymers via emulsion polymerization, their incorporation into colloidal particles is difficult to handle. The primary reason is the immiscibility between hydrophobic C-F entities and the continuous aqueous phase resulting from large surface tension differences.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the progressive availability of differently fluorinated (meth)acrylic monomers has resulted in an increasing interest for the polymers which may be produced from them, essentially because they exhibit a wide range of improved and peculiar characteristics [2,3]. The formal replacements of hydrogen atoms with fluorine atoms either in the main chain or in the alkyl side groups improves thermal-and photo-oxidative stability and modify drastically other properties, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The delay of antisticking layer degradation by the surfactant can be explained by the segregation or migration of the surfactant molecules to the resin surface. Some fluorinated compounds, when added to the resin in small amounts, are known to significantly increase the water contact angles of the resin layer because of the fluorine compound segregation [55,[57][58][59][60]. Wu et al revealed that the driving force for surfactant segregation to the mold-resin interface was largely dependent on the surface energy and polarity of the mold [55], and that the lowest polarity surfaces such as the FSAM(fluorinated self-assembled monolayer)-treated quarts mold surface had the greatest effect on surfactant segregation, whereas little surfactant segregation was observed in the case of the untreated quarts mold.…”
Section: Evaluation Of Mold Durability By Step and Repeat Uv Nanoimprintmentioning
confidence: 99%